The Association of Adult Muslims’ Spirituality with Alcoholism: A Cross-Sectional Study - Nur Hidayati; Indra Ningrum; Aprelia Afidatul Hanafi; Neil Madulara Martin (GLOBAL HEALTH SCIENCE GROUP, 2026)
Alcohol consumption among adolescents and young adults continues to increase. Excessive alcohol consumption can causepoisoning or overdose as well as ventricular rhythm disturbances and fatal tachyarrhythmias, which can increase the risk of sudden death. Objective: This study aims to determine the relationship between Muslims’ spirituality and alcohol consumption. Cross-sectional design on 100 Muslims who consumed alcohol, selected by using the total sampling technique. Data was collected in April 2025 through online questionnaires by using Google Forms. The Daily Spiritual Experience Scale (DSES) (Cronbach alpha 0.94), Muslim Religious Practices (Cronbach alpha 0.80), and the Alcohol Use Disorders Identification Test (AUDIT) (Cronbach alpha 0.86) are the instruments for the questionnaire. The collected data were analyzed using the Pearson Test (α ≤ 0.05). This study shows that 62% of the population has moderate spirituality, 64% of the population has moderate Muslim spirituality, and 54% of the population were categorized as alcohol dependent. There was a strong correlation between spirituality and alcohol consumption habits (p=0.000, r=0.412). There was a very strong correlation between Muslim spirituality and alcoholism (p=0.000, r=0.927). These findings indicate that the lower the personal level of spirituality, the higher an individual’s tendency to consume alcohol excessively.